Mortality Rate of Sepsis Patients in the Intensive Care Unit: The Prognostic Role of Ejection Fraction and Procalcitonin: - Hejazi, Mohammad Esmaeil; Samadi Takaldani, Ali Hossein; Ranjbar, Abdolmohammad; Negaresh, Mohammad; Hejazi, Yasin (Galen Medical Journal, 2021)
.